(untitled) (International Journal of Engineering & Extended Technologies Research (IJEETR), 2026)
Fault localization is one of the most expensive, tedious and time consuming activities in network. Fault localization is the process of finding the exact source of failure from a set of failure indications with minimal human intervention. This demand has led to the proposal and development of various methods each of which seeks to make the fault localization process more effective in its own unique and creative way. In this paper we provide an overview of several such methods and discuss some of the key issues and concerns that are relevant to fault localization